2013
DOI: 10.1002/joc.3763
|View full text |Cite
|
Sign up to set email alerts
|

Changes in temperature and precipitation extremes over the Greater Horn of Africa region from 1961 to 2010

Abstract: Recent special reports on climate extremes have shown evidences of changes in the patterns of climate extremes at global, regional and local scales. Understanding the characteristics of climate extremes at regional and local levels is critical not only for the development of preparedness and early warning systems, but is also fundamental in the development of any adaptation strategies. There is still very limited knowledge regarding the past, present and future patterns of climate extremes in the Greater Horn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
133
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(169 citation statements)
references
References 103 publications
31
133
2
3
Order By: Relevance
“…The diurnal temperature ranges on the other hand depict decreasing trends. The results of this study are in a general agreement with those obtained by earlier researchers [9] and [10] who used data for one station in the area. However, for this area of study, it is noted that the magnitudes of change of the indices are location specific and therefore the information is more reliable for application in planning and decision making for the specific locations analysed.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The diurnal temperature ranges on the other hand depict decreasing trends. The results of this study are in a general agreement with those obtained by earlier researchers [9] and [10] who used data for one station in the area. However, for this area of study, it is noted that the magnitudes of change of the indices are location specific and therefore the information is more reliable for application in planning and decision making for the specific locations analysed.…”
Section: Resultssupporting
confidence: 92%
“…The information on these trends is critical in decision making with regard to agricultural planning and practice. Attempts have been made by some researchers to derive these indices [9] and [10] for the country. However, these studies have relied on data of only one station from this area of study.…”
Section: Introductionmentioning
confidence: 99%
“…The MarchApril-May season had the highest but statistically insignificant decline in seasonal rainfall amounts. The University of East Anglia Climate Research Unit gridded observational datasets were well correlated to the observed rainfall data in regions without rainfall stations, which agrees with the work by Endris et al (2013) and Omondi (2014).…”
Section: Discussionsupporting
confidence: 89%
“…Long-rain declines have been confirmed by many recent studies Liebmann et al, 2014;Lyon and DeWitt, 2012;Viste et al, 2012), and corroborated by analyses of normalized difference vegetation index imagery (Pricope et al, 2013) and satellite-observed soil moisture (Omondi et al, 2013 Nicholson (2014b). The source of the SST forcing behind these recent East African rainfall declines, however, continues to be a matter of considerable debate.…”
Section: Climate Change and Pacific Decadal Variability (Pdv)mentioning
confidence: 75%